Behavior of Yb3+ and Er3+ during Heat Treatment in Oxyfluoride Glass Ceramics. (2nd January 2014) - Imanieh, M. H.; Martín, I. R.; Gonzalez-Platas, J.; Eftekhari Yekta, B.; Marghussian, V. K.; Shakhesi, S.
Abstract : The effects of alumina content and heat treatment on upconversion properties of codoped (ErF3 -YbF3 ) oxyfluoride glass ceramics were investigated. Results showed that alumina content had an effect on phase separation and viscosity of the glass. Due to the high viscosity of low alumina content glass, the phase separated areas were smaller in these specimens. Increasing the heat treatment temperature led to the incorporation of Er 3+ ions into CaF2 crystals and also increased the Yb 3+ concentration in them. This increase improved the energy transfer and back transfer process between Er 3+ and Yb 3+ ions and as result upconversion intensity was increased.